“When I woke up I was so worried and ashamed, I thought it was a disease”: Adolescent boys’ transitions through puberty in Kenya - Carney, Allison; Mulei, Titus; Kurao, Daniel; Hagstrom, Christine; Sommer, Marni (Frontiers in Reproductive Health, 2022)
Growing evidence suggests a need for more focused attention on boys’ experiences of puberty in sub-Saharan Africa to assure healthy transitions into young adulthood. Existing research remains limited on the masculinity norms shaping boys’ maturation experiences in Kenya. To help fill this gap, we conducted a comparative case study using qualitative methodologies with 16–19-year-old male youth in rural and urban Kenya, and with adults interacting in boys’ daily lives. Findings suggest that Kenyan boys experience shame, confusion and silence around changes happening in their bodies; face pressures from new societal expectations as they become young men; and have adolescent lives shaped by minimal supervision, increased peer pressures and engagement in more risky health behaviors. Additional research and targeted interventions on boys transitioning through puberty and early adolescence are needed to better understand their vulnerabilities and prevent or reduce their engagement in unsafe behaviors.